Scanning Electron-Microscopy (SEM) of lightweight alloys - Tan, Wei Jian (Nanyang Technological University, 2022)
With the constant improvement and evolution in technology, higher importance is placed on the materials. Aluminium, the most plentiful metal found in the earth’s crust, has been widely used in the automotive and aerospace industry due to its lightweight and corrosion-resistance properties. Aluminium is combined with other metals to form aluminium alloys for properties that suit different applications. The objective of this project was to study the microstructure of the specimen, aluminium 6061 after it had undergone tensile testing. The specimen would go through a series of metallographic preparation processes which consist of cutting, mounting, grinding, polishing, and etching to prepare it for Scanning Electron Microscopy (SEM). The microstructure of the specimen will first be observed under the Optical Microscope at magnifications of 5X and 10X and followed by Scanning Electron Microscopy (SEM) at higher magnifications. The results and images obtained from the Scanning Electron Microscopy (SEM) will be examined and compared with results from professional researchers to validate the results.